Using Spreadsheets to Map a Library Reclassification, Reorganization, and Merger - Stepanie Wright; Nancy Blase (Issues in Science and Technology Librarianship)
With the approaching merger of two university branch libraries, library staff took the opportunity to reclassify and reorganize the collections being integrated. The materials were reclassed from Dewey Decimal to Library of Congress, and the books and periodicals were integrated from separate shelving areas into one continuous call number sequence. The library remained open and maintained normal service levels throughout the process including during the merger itself. This case study details how an academic science library found spreadsheets to be superbly versatile and valuable for manipulating and visualizing data -- from planning through implementation. [ABSTRACT FROM AUTHOR]